Finding the Truth in Politics: An Empirical Validation of the Epistemic Political Efficacy Concept. Issue 1 (1st January 2018) - Farman, Lisa; Riffe, Daniel; Kifer, Martin; Leder Elder, Sadie
ABSTRACT: Self-efficacy theory suggests that one's perceived ability to successfully find facts may motivate political information seeking. A telephone survey of voters in a presidential campaign attempted to further validate the concept of epistemic political efficacy (EPE), or belief one can discover the "truth" in politics, and applied it to modern information-seeking behaviors. This study of North Carolina registered voters ( N = 605) demonstrates that EPE adds predictive power beyond commonly used measures such as individual political efficacy for contemporary media use variables like online information seeking and partisan cable viewing. EPE was a stronger positive predictor of online information seeking than individual political efficacy. In addition, viewing partisan cable shows had a stronger relationship with EPE than mainstream TV news viewing, and EPE significantly predicted MSNBC viewing, even after controlling for partisanship. In a word, voters who are high in the belief that political facts or "truths" exist take steps to find and understand them.